Annotated checklist of new additions to the Andean flora of Moquegua, Peru - Montesinos Tubée, Daniel B. (2012)
New records of 103 species reunited in 79 genera and 33 families are presented for the flora of the upper basin of the Tambo-Ichuña Rivers in the General Sánchez Cerro Province in the Department of Moquegua. With this study the flora of the northern Andean region of Moquegua rises to 507 species, contained in 271 genera and 75 families. The number of endemic species rises compared to the results obtained in 2011 by the author. This percentage of endemism is one of the highest documented for the department of Moquegua. Comments on nomenclature are also highlighted for the species documented as well as the herbarium collections reviewed and the geographical area where it was found. This new contribution to knowledge of the country's flora is the result of field work and herbarium reviews made from 2009 through 2012, mentioning also, elements of flora that were not previously identified to species level (Montesinos, 2011). Revisions and botanical comparisons were made at the herbaria HUSA, USM and the virtual images of F and MO.